Leadership Ethics and its Role in Achieving Social Responsibility An Analytical Study of the Opinions of a Sample of Administrative Leaders in Shopping Centers in the City of Sulaymaniyah - Omer Mustafa Mohammed; Soran Mohammed Saeed (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The research aims to determine the nature of the correlation and the relationship of the impact of ethical leadership and social responsibility among the leaders and managers in the shopping centers in the city of Sulaymaniyah. And dealt with this research with modern administrative style. In this research the researchers relied on the (ethical leadership) variable key independent included three dimensions represented by (the availability of ethical, practice of ethic, promote and strengthen ethic) and dependence variable the main effector (social responsibility), which included three dimensions represented by (b responsibility towards society, the responsibility towards the customer, the responsibility towards the environment). The researchers chose a group Malls and Super Market, which increased their interest by buyers and increased their number. Since the goal of current research is to find out the relationship and the impact of the link between ethical leadership and social responsibility. The adoption of the researchers on the style of the stratified random sample, one of the statistical methods used in the selection of appropriate research sample and the most accurate representation of the community. In light of this issue were distributed (70) to identify for fear of the potential drop in the rate of retrieval or the presence of questionnaires unsuitable for a dump, as the numbers of valid questionnaires were retrieved and statistical analysis (53) questionnaire. The research concluded find a set of appropriate recommendations can be benefit mainly in the respective organizations (supermarkets and malls) in the center of sulaimany city.